Elderly people affected by tuberculosis in the Etate of Paraíba from 2009 to 2019 (Research, Society and Development, 2021)
This research aimed to analyze the factors associated with sex, clinical aspects and associated diseases and disorders in elderly people with tuberculosis in Paraíba. This was an epidemiological, observational, retrospective, analytical and documentary study, with data collection at the Informatics Department of the Unified Health System (DATASUS). The variables year, sex, age group (60-69, 70-80 or +), clinical aspects and immunosuppressive factors were evaluated. Data were analyzed using the Statistical Package for Social Sciences (SPSS) software, together with Microsoft Excel and Word for the collection, organization and creation of graphs and tables, as well as EpiInfo 7 for analysis of linear trends. The total sample consisted of 2,037 cases, with the majority in the elderly aged 60-69 years (58%) and male (65%). In immunosuppressive factors, it was noted that alcoholism and smoking were more related to men (19% and 10%, respectively), while diabetes was more related to women (24%). Females are more affected by extrapulmonary TB (14%) and males are more affected by pulmonary TB (89%). Thus, the epidemiological profile of TB in senile in the state of Paraíba is men, aged between 60-69 years, with the presence of comorbidities and lifestyles such as alcoholism and predominant smoking. Immunosuppressive factors, such as HIV/AIDS, are predominant for pulmonary TB.